Evaluasi Program Pembelajaran Guru Guna Mengoptimalkan Peran Guru Sebagai Pendidik - Inom Nasution; Anggun Sari Fadilla; Isma Hayati; Dawi Nurjannah; Accep Noor Akbar Sambo; Arif Abdul Gani Lubis; Gani Lubis (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine how influential evaluation is in a teacher's learning method in order to be able to improve student learning outcomes. Data collection uses reference collection methods in the form of reading materials such as books and scientific journal articles, which use a qualitative research approach. The results of this study will show that as an educator the teacher must be able to (1) create a conducive classroom atmosphere, (2) arrange teachers to train student discipline, (3) provide learning methods that can increase student interest in learning. And all of this can easily be done by a teacher if he carries out a learning evaluation, with this evaluation it will make it easier for the teacher to see how far the results of the teacher's performance have been. The results in question are good, not good, useful, or not useful and so on. It is important to know the results of learning because it can be a guide for educators to find out how far the learning process that they are doing can develop the potential of students.